2015
DOI: 10.1002/dac.3004
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative multi‐cellular large MIMO over asynchronous channel training

Abstract: SUMMARYThis work analyzes multi-cell MIMO systems equipped with a very large number of antennas in the basestation (BS) side and with low-complexity zero-forcing and matched-filter receivers. Cooperation between BSs in a multi-cell scenarios is analyzed in order to avoid the well-known pilot contamination effect on massive MIMO systems, while the effects of asynchronism between users and BSs in training phase using different pilot sequences, for example, Walsh-Hadamard, Gold, and Kasami sequence sets on the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…𝜅 = 0, these two algorithms have almost the same performance. From Equation (21), it can be seen that p min effects the transmit power p k l (∀k ∈ , l ∈  k ). With the increasing of 𝜅, p min becomes the dominate element to the transmit power, and decreases the system performance.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…𝜅 = 0, these two algorithms have almost the same performance. From Equation (21), it can be seen that p min effects the transmit power p k l (∀k ∈ , l ∈  k ). With the increasing of 𝜅, p min becomes the dominate element to the transmit power, and decreases the system performance.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…However, it has not been considered in existing schemes. Besides, CSI acquired at nodes were also supposed to be perfect, which is rather unrealistic, as errors would be inevitably introduced by channel estimation, channel quantization or feedback delay in practice [21][22]. The above facts motivate this paper to study on the fairnessaware nonlinear transceiver design under the per-node power constraints, and further on the robust scheme with imperfect CSI for EH-powered CoMP systems.…”
Section: Contributionsmentioning
confidence: 99%
“…Without loss of generality, it is assumed that 0 = τ 11 11 < τ 12 11 < τ 21 11 < τ 22 11 < T where T is the symbol duration. For simplicity of illustration, the transmitted signals are depicted with a rectangular pulse shape in Fig.…”
Section: A 2-cell 2-user Scenariomentioning
confidence: 99%
“…We intentionally create timing mismatch between different received signals. While asynchronous channel training method in [11] has resulted in erroneous estimated channel because of noise and channel correlation, we show how to avoid the drawbacks by designing an appropriate sampling method. It has been shown that the performance of MIMO systems with intentional timing offset between transmitters can be improved by using sampling diversity [12][13][14][15].…”
mentioning
confidence: 99%
“…By their network model, these works can be divided into two main groups: cooperative and noncooperative. The former assumes that base stations of different cells, in order to increase the total capacity, share their information like channel state information or users data [1][2][3][4][5][6][7][8][9][10]. For example, in [3], sum-rate for the multicell vector perturbation precoding in the case of uniformly distributed input and an asymptotic upper bound on the sum-rate at high signal-to-noise ratios are derived.…”
Section: Introductionmentioning
confidence: 99%